2014
DOI: 10.1016/j.cell.2014.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Mapping and Characterization of Notch-Regulated Long Noncoding RNAs in Acute Leukemia

Abstract: Accumulating evidence demonstrated that while a small minority of the human genome encodes proteins a large portion of the genome encodes non-protein coding transcripts. Thus it has been suggested that such RNAs, including the recently described family of long non-coding RNAs (lncRNA) are key regulators of cellular homeostasis and transformation leading to tumorigenesis. Here we tested this hypothesis focusing on the role of lncRNAs in T cell leukemia (T-ALL), a pediatric blood cancer, characterized by Notch p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
344
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(356 citation statements)
references
References 72 publications
(94 reference statements)
9
344
0
3
Order By: Relevance
“…lncRNAs have been described to be able to regulate gene expression of neighboring genes (48,49). We, therefore, asked if the expression of the most proximal genes upstream and downstream from MINCR were changed after MINCR knockdown.…”
Section: Mincr Regulates Cell Cycle Progression By Controlling the Exmentioning
confidence: 99%
“…lncRNAs have been described to be able to regulate gene expression of neighboring genes (48,49). We, therefore, asked if the expression of the most proximal genes upstream and downstream from MINCR were changed after MINCR knockdown.…”
Section: Mincr Regulates Cell Cycle Progression By Controlling the Exmentioning
confidence: 99%
“…22,23 Differential expression analysis of lincRNAs in ALL patients compared to healthy controls revealed 197 lincRNAs were differentially expressed (Table S4). Among them, 104 lincRNAs were upregulated and 93 were downregulated in ALL.…”
Section: Differential Expression Of Transcripts With Epigenetic Regulmentioning
confidence: 99%
“…Although heritable changes in gene regulation that occur via modification of the DNA without changes to the DNA sequence are often referred to as epigenetic programming, noncoding RNA (ncRNA)-mediated transcriptional or posttranscriptional regulation is one of the major regulation mechanisms for epigenetic programming (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Recent studies have identified thousands of long ncRNAs (lncRNAs) (17,23) in mammalian genomes that regulate gene expression in a variety of immunological processes (31)(32)(33)(34)(35), such as differentiation of T cells (33,36) and dendritic cells (DCs) (35).…”
Section: T Uberculosis (Tb) Caused By Mycobacterium Tuberculosis (Mtb)mentioning
confidence: 99%